Quality Of Work Life On The Tegallalang Gianyar Kesmas Technical Service Unit - Sudirman, I Made; Kepramareni, Putu; Suardhika, I Nengah (The journal of contemporary issues in business and government, 2021)
The achievement of optimal employee performance based on good behavior from individual motivation and working conditions in the organization is becoming increasingly important. This research was conducted to examine and explain the role of motivation and quality of work life (in the application of organizational citizenship behavior in the workplace, and its impact on employee performance. This research was conducted with a survey approach to employees who work at the Public Health Technical Service Unit in Tegallalang Gianyar with a sample of all employees, as many as 73 people. Data were obtained from distributing questionnaires, then analyzed using SEM with the Smart-PLS software program. The findings obtained from the results of the analysis carried out that the motivation possessed by employees at work is not able to determine the increase in employee performance at Tegallalang Gianyar Public Health Unit. However, the work motivation of employees who are able to underlie OCB can determine better employee performance. Meanwhile, the quality of work life of employees is able to directly determine the increase in employee performance. However, the quality of work life which is good and can underlie OCB turns out to be able to produce greater performance achievements of employees at the Public Health Technical Service Unit in Tegallalang Gianyar.